Dinamika Pariwisata Halal: Peluang dan Tantangan Pariwisata Ramah Muslim di Indonesia - Hanin Nur Laili (STIT Syekh Muhammad Nafis Tabalong, 2025)
The halal lifestyle has been growing globally over the past two decades. Due to globalization, the halal lifestyle is not limited to food but also extends to other products and services such as tourism. There are many forms of halal tourism or Muslim-friendly tourism in Indonesia. In its dynamics, there are various pros and cons regarding the implementation of Muslim-friendly tourism in Indonesia. This study attempts to map the opportunities and challenges of Muslim-friendly tourism in Indonesia. The research method used is descriptive qualitative. The results of this study show several opportunities and challenges for Muslim-friendly tourism in Indonesia. Among the opportunities are: (1) Indonesia's large Muslim population, (2) a Means of introducing Indonesia to global Muslim tourists, (3) Significant economic benefits supported by the Indonesian Halal Industry Master Plan (MPIHI), and (4) Digital promotion as a medium to attract tourists. Meanwhile, the challenges are: (1) Resistance from non-Muslim communities, (2) Uneven government support, and (3) MSMEs not being major players in the development of Muslim-friendly tourism.